A note on the brazilian cross-state debt connectedness - Pinheiro Junior, Raimundo Nunes (2022)
We address the cross-state indebtedness (DCL/RCL) variation connectedness using 89 bimonthly data from 2006b6 to 2021b4, based on the indices proposed by Diebold and Yilmaz (2009, 2012, 2014). This framework enables us to infer about the direction, and the strength of bilateral spillovers for a large number of simultaneously interacting variables in a clear and compact manner. We are able to identify the most influential states in each region, as well as the region with the highest total connectedness. This empirical exercise allows us to discuss the possible influence between state governments in conducting public policies associated with indebtedness. The results help us to better understand the consequences of total and directional indebtedness spillover across states in Brazil.